Effect of Osteochondroplasty on Time to Reoperation After Arthroscopic Management of Femoroacetabular Impingement: Analysis of a Randomized Controlled Trial. Issue 4 (5th April 2022) - Kay, Jeffrey; Simunovic, Nicole; Ayeni, Olufemi R.; ,; Bhandari, Mohit; Bedi, Asheesh; Järvinen, Teppo; Musahl, Volker; Naudie, Douglas; Seppänen, Matti; Slobogean, Gerard; Thabane, Lehana; et al.
Background: A subset of patients with femoroacetabular impingement (FAI) fail arthroscopic management. It is not clear which patients will fail surgical management; however, several surgical and patient factors, such as type of procedure and age, are thought to be important predictors. Purpose: This time-to-event analysis with a 27-month follow-up analysis compared the effect of (1) arthroscopic osteochondroplasty with or without labral repair versus (2) arthroscopic lavage with or without labral repair on the time to reoperation in adults aged 18 to 50 years with FAI. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: Eligible participants had been randomized in a previous study trial to a treatment of arthroscopic osteochondroplasty or arthroscopic lavage with or without labral repair. Using the comprehensive data set from the Multinational Femoroacetabular Impingement Randomized controlled Trial, all reoperations until 27 months after surgery were identified. The analysis was conducted using a Cox proportional hazards model, with percentage of patients with a reoperation evaluated in a time-to-event analysis as the outcome. The independent variable was the procedure, with age and impingement subtype explored as potential covariates. The effects from the Cox model were expressed as the hazard ratio (HR). All tests were 2-sided, with an alpha level of .05. Results: A total of 108 patients in the osteochondroplasty group and 106 patients in the lavage group were included. The mean age of the patients included in the study was 36 ± 8.5 years. Overall, 27 incident reoperations were identified within the 27-month follow-up, with an incidence rate of 6 per 100 person-years. Within the osteochondroplasty group, 8 incident reoperations were identified (incidence rate, 3.4 per 100 person-years), while within the lavage group, 19 incident reoperations were identified (incidence rate, 8.7 per 100 person-years). The hazard of reoperation for patients undergoing osteochondroplasty was 40% of that of patients undergoing lavage (HR, 0.40 [95% CI, 0.17-0.91] P = .029). Conclusion: This study demonstrated that for adults between the ages of 18 and 50 years with FAI, arthroscopic osteochondroplasty was associated with a 2.5-fold decrease in the hazard of reoperation at any point in time compared with arthroscopic lavage. Registration: NCT01623843 (ClinicalTrials.gov identifier).